Perinatal Exposure to Phenols and Poly- and Perfluoroalkyl Substances and Gut Microbiota in One-Year-Old Children - Davias, Aline; Lyon-Caen, Sarah; Rolland, Matthieu; Iszatt, Nina; Thomsen, Cathrine; Haug, Line Småstuen; Sakhi, Amrit Kaur; Monot, Celine; Rayah, Yamina; Ilhan, Zehra Esra; Jovanovic, Nicolas; Philippat, Claire; et al. (Environmental science & technology, 2024)
The role of the gut microbiota in human health calls for a better understanding of its determinants. In particular, the possible effects of chemicals with widespread exposure other than pharmaceuticals are little known. Our aim was to characterize the sensitivity of the early-life gut microbiota to specific chemicals with possible antimicrobial action. Within the SEPAGES French couple-child cohort, we assessed 12 phenols in repeated urine samples from 356 pregnant women and their offspring and 19 poly- and perfluoroalkyl substances (PFASs) in serum from the pregnant women. We collected stool samples from the children at one year of age, in which the V3-V4 region of the 16S rRNA gene was sequenced, allowing for gut bacterial profiling. Associations of each chemical with α- and β-diversity indices of the gut microbiota and with the relative abundance of the most abundant taxa were assessed using single-pollutant and mixture (BKMR) models. Perinatal exposure to certain parabens was associated with gut microbiota α- and β-diversity and with Firmicutes and Proteobacteria. Suggestive associations of certain phenols with genera of the and families were observed, but these were not maintained after correction for multiple testing. Parabens, which have known antimicrobial properties, might disrupt the child gut microbiota, but larger studies are required to confirm these findings.